My love mix-up! Vol. 3 - Hinekure, Wataru (Shojo beat manga., 2022)
"Aoki has a crush on Hashimoto, the girl in the seat next to him in class. But he despairs when he borrows her eraser and sees she's written the name of another boy--Ida--on it. To make matters more confusing, Ida sees Aoki holding that very eraser and thinks Aoki has a crush on him! Aoki has a crush on Ida, a boy in his class. Ida has learned from Akkun the story behind Hashimoto's eraser--that Aoki told Ida he liked him to protect Hashimoto's secret crush. The only trouble is that Aoki really does like Ida, so now Aoki has to confess his love to Ida all over again!"--Amazon.